Can mitogenomes of the Northern Wheatear (Oenanthe oenanthe) reconstruct Its phylogeography and reveal the origin of migrant birds? - Wang, Erjia; Zhang, Dezhi; Braun, Markus S.; Hotz-Wagenblatt, Agnes; Pärt, Tomas; Arlt, Debora; Schmaljohann, Heiko; Bairlein, Franz; Lei, Fumin; Wink, Michael (Scientific reports, 2020)
The Northern Wheatear (Oenanthe oenanthe, including the nominate and the two subspecies O. o. leucorhoa and O. o. libanotica) and the Seebohm’s Wheatear (Oenanthe seebohmi) are today regarded as two distinct species. Before, all four taxa were regarded as four subspecies of the Northern Wheatear. Their classification has exclusively been based on ecological and morphological traits, while their molecular characterization is still missing. With this study, we used next-generation sequencing to assemble 117 complete mitochondrial genomes covering O. o. oenanthe, O. o. leucorhoa and O. seebohmi. We compared the resolution power of each individual mitochondrial marker and concatenated marker sets to reconstruct the phylogeny and estimate speciation times of three taxa. Moreover, we tried to identify the origin of migratory wheatears caught on Helgoland (Germany) and on Crete (Greece). Mitogenome analysis revealed two different ancient lineages that separated around 400,000 years ago. Both lineages consisted of a mix of subspecies and species. The phylogenetic trees, as well as haplotype networks are incongruent with the present morphology-based classification. Mitogenome could not distinguish these presumed species. The genetic panmixia among present populations and taxa might be the consequence of mitochondrial introgression between ancient wheatear populations.